2020
DOI: 10.1111/nyas.14522
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory challenges with biosimilars: an update from 20 countries

Abstract: The World Health Organization (WHO) issued guidelines for the regulatory evaluation of biosimilars in 2009 and has provided considerable effort toward helping member states implement the evaluation principles in the guidelines into their regulatory practices. Despite this effort, a recent WHO survey (conducted in 2019-2020) has revealed four main remaining challenges: unavailable/insufficient reference products in the country; lack of resources; problems with the quality of some biosimilars (and even more with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 9 publications
0
50
0
Order By: Relevance
“…The recent studies reported in the literature suggest that the regulatory challenges in biosimilar space continue to be a topic of interest and deserves further debate. However, our study, in comparison to existing knowledge in the area, provides insight about TITCK (Turkey) and COFEPRIS (Mexico) agencies pertaining to biosimilar development challenges, in addition to the 20 countries included in the WHO survey reported by Kang et al ( 27 ). The findings reposted by Garcia et al ( 28 ) of Latin America are complemented by this study for challenges pertaining to biosimilar approval pathway.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The recent studies reported in the literature suggest that the regulatory challenges in biosimilar space continue to be a topic of interest and deserves further debate. However, our study, in comparison to existing knowledge in the area, provides insight about TITCK (Turkey) and COFEPRIS (Mexico) agencies pertaining to biosimilar development challenges, in addition to the 20 countries included in the WHO survey reported by Kang et al ( 27 ). The findings reposted by Garcia et al ( 28 ) of Latin America are complemented by this study for challenges pertaining to biosimilar approval pathway.…”
Section: Discussionmentioning
confidence: 89%
“…The non-acceptance of global clinical data and repetition of clinical studies mandatorily in local population by these regulatory agencies adds to unnecessary development costs ( 34 ). Such duplication of studies further is likely to impact the overall biosimilar development process and approval timelines in these countries ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, the World Health Organisation (WHO) Expert Committee on Biological Standardization created a set of recommendations and guidelines to help its member states implement regulation of biologics and biosimilars. However, member states still face regulatory challenges, based on a 2019-2020 WHO survey of participants in 20 countries (Kang et al, 2021) more specifically related to reference biologics, including limited access to information on the reference biologic, financial constraints due to the price of the reference biologic, and difficulty of obtaining reference biologic samples to assess comparability. The authors noted some countries accept reference biologics that are foreign-licensed and -sourced, whereas others require a domestically licensed reference product or bridge studies for a foreign-sourced reference product, which are costly and often result in unnecessary duplication of studies (Rahalkar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Such efforts could increase confidence in and acceptance of using biosimilars in medical practice to fully capture the societal and patients benefits offered by biosimilars. Non-European regulatory authorities can use EPARs to support their own decision-making process, relying on the regulatory assessment undertaken by competent authorities in the world [67][68][69][70][71][72]. Therefore, EPARs could contribute to accelerating the regulatory review process and patients access to biosimilars in non-European jurisdictions.…”
Section: Discussionmentioning
confidence: 99%